CREDIT AND PAYMENT SYSTEMS IN COOPERATIVE EMPLOYEES INSTALLMENT JARAHNITRA MICROSOFT VISUAL BASIC 6.0 MENNGUNAKAN - Dira Supriana; Cut Asiana Gemawaty, SKom, MMSI (Jurnal Sistem Informasi, 2005)
In addition to the rapid development era the more complex problems faced mannusia.The necessity to solve a problem quickly, accurately and efficiently is very necessary.Therefore, information science and technology is always developed to make ithappen.The role of computer membarikan a huge impact to human life, as evidence of almostall types of businesses use computers as a tool to speed up data processing. Amongthe economic sector in the process of granting credit or installment loans andcalculations that must be paid at the cooperative.In this study, the authors make a computerized system for credit granting process inthe form of loans or credit goods that accompanied the installment payments onCooperative Jarahnitra using Microsoft Visual Basic 6.0 to help accelerate theprocess of data processing.